Correlation between academic self-efficacy and digital competence: an empirical study on first year students - Fris Okta Falma; Ade Herdian Putra (Journal of Counseling, Education and Society, 2025)
This study aims to investigate the relationship between Academic Self-Efficacy (ASE) and Digital Competence (DC) among first-year university students. The background of this study is based on the importance of digital skills in the modern educational era and the role of academic self-efficacy in facilitating the mastery of these skills. This study used a quantitative approach with a correlational analysis method. The population of this study was first-year students, with samples taken randomly. The research instrument used was a scale designed to measure both constructs. The data analysis technique was carried out with partial least squares (PLS) technique to test the proposed hypothesis. The results showed that there is a significant and positive relationship between academic self-efficacy and digital competence, where an increase in academic self-efficacy contributes to an increase in students' digital competence. The conclusion of this study confirms the importance of developing academic self-efficacy as a strategy to improve digital skills. It is suggested that educational institutions design programs that support the development of students' academic self-efficacy, in order to improve their digital competence in an increasingly technology-dependent era.